A influência das características do projeto de crowdfunding na taxa de sucesso das campanhas da modalidade sem retorno financeiro no Brasil - Oliveira, Messias Elmiro Gomes Loiola de (2022)
In the beginning of the century XXI, the crowdfunding (crowdfundig) it became popular as a way of intermediating financial resources from supporters destined for receiver projects as a collaborative economy tool. In this perspective, the study aim to analyze the influence of the project characteristics on the success rate of crowdfunding campaigns without financial return in Brazil. For data analysis, we examined a sample of 1,744 completed projects on the Catarse platform, from 2011 to 2021. To test the hypotheses, descriptive analysis, correlation and multiple linear regression using the Least Squares Method (LSM) were used. To test the relationship, the following were used as constructs related to the particularities of the project: the characteristics of the campaign, the receiver and the Brazilian region. As a measure of the success of the campaign, a continuous dependent variable was used, which results from the equation amount collected, divided by the stipulated target. The results show that campaign characteristics - such as goal, number of supporters, type of campaign and budget details - influence the success rate of crowdfunding. The characteristics of the receiver also influence the success rate, namely: type of product, artistic purpose, experiences in previous campaigns, personal identification and gender of the receiver. It was also verified that the location of the project influences the success of crowdfunding, with higher success rates in more populous municipalities, in the South and Southeast regions of the country and in projects based in the interior of the states. The research contributes to developing strategies to attract resources for those interested in financing projects through crowdfunding without financial return.